Factors influencing the Prevalence and pathogenicity of Trichomonas vaginalis - Al-Kaisi, Aroub Abdul Rahman; Al- Janabi, Bahjat; Al-Tikriti, Raja (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Trichomonas vaginalis is a common parasite of both male and female genital tracts. Transmission of the infection is mainly by sexual intercourse; however contaminatedtowels, douche equipments, examination instruments and other objects may be responsible for some infections.Aim: Is to study the influence of some factors that affect the spread of this parasite such as socioeconomic status, marital status, pregnancy and parity …….etc.Methods: The study was conducted in the period from November 1992 to August 1993 on 480 female patients presented with vaginal discharge with or without itching, compared to 50 females complaining of gynecological problems other than infections. Investigations carried out during this study include: .Wet mount examination.,.Culture on artificial media.,Examination of fixed stained smear with: a.Gram's stain.b.Leischman's stain.c.Giemsa's stain.d.Papanicolaou's stained smear.4. Measuring the PH of the vaginal discharge or the PH of the vaginal side wall. Results: The effect of some factors on the prevalence and pathology of Trichomonas vaginalis was evaluated in this study. Among different socioeconomic groups, the higher infection rate (65.22%) was seen in the low socioeconomic group. The infection rate of trichomoniasis was found to be higher among married females (19.81%), than divorced (16.66%), widowed(12.5%) or singles (11.11%). Regarding the menstrual cycle, infection with Trichomonas vaginalis was found to be increasing during the postmenstrual phase of the cycle (24.21%)compared to the infection rate obtained from patients in the premenstrual phase of the cycle (16.09%). A higher infection rate was reported among non pregnant females (20%) thanpregnant (9.09%).Females using different contraceptive measures showed an infection rate of (28.88%), which was higher than that reported among those not using any contraceptivemeasures (18.95%). The PH values of the vaginal discharge were measured in 90 patients and the highest infection were seen at PH values 6.0 (28.88%) and 5.5 (20%) respectively.Conclusion: The spread of Trichomonas vaginalis infection may be affected by many factors such as socioeconomic status, marital status, pregnancy status and parity, phase of themenstrual cycle, the use of different contraceptive measures and the PH values of the vaginal discharge..